My Hero Academia. Vol. 22, That which is inherited - 1986-; Cook, Caleb D (Shonen Jump manga., 2019)
Midoriya inherits the superpower of the world<U+2019>s greatest hero, but greatness won<U+2019>t come easy. What would the worl